Downtown Sites of Huntington Beach - Watkins, Howard::::::::: (1988)
View of buildings on Pacific Coast Highway between 6th and Main Streets Businesses include: Pizza Centre, Wimp's, liquor store, ??, and Jack's Surfboards; future location on InnOcean